EXPERIMENTAL MIXTURE DESIGN FOR MOLDING CASTING IN A FERROUS FOUNDRY - Granado Ojito, Jany; Morales Pérez, Mayra Caridad; Mollinedo Nodarse, Pedro Jorge; Rosa Domínguez, Elena R. (Centro Azúcar Journal, 2026)
Introduction: Ferrous foundries are significant pollution sites due to manual molding and shakeout processes that generate large volumes of waste sand, justifying the need to reinforce sustainable development policies through reuse alternatives. Objective: To evaluate an experimental mixture design for molding iron castings at the "9 de Abril" Factory in Sagua la Grande. Materials and Methods: A designed experiment based on the simplex lattice method was applied, incorporating waste sand into new mixtures. The software STATGRAPHIC Centurion 16.1.8 was used to analyze the influence of each component on mold properties, obtain mathematical models, and perform multivariable optimization. Results and Discussion: Statistical analysis showed that the special cubic model provides the best fit for permeability and strength, while the quadratic model was most suitable for moisture. Technical optimization determined a mixture with 38% return sand, 34% arimao sand, and 28% bentonite. However, economic optimization reduced costs by 35.4% by increasing return sand (49.1%) and decreasing bentonite (14.1%), while keeping properties within established quality parameters. Conclusions: Incorporating waste sand into molding mixtures proved technically feasible, meeting the required quality parameters, achieving a 49.1% reuse of return sand, a 35.4% cost reduction, and consolidating this alternative as a circular economy practice.